2019
DOI: 10.1186/s13244-019-0789-4
|View full text |Cite
|
Sign up to set email alerts
|

Chest imaging using signs, symbols, and naturalistic images: a practical guide for radiologists and non-radiologists

Abstract: Several imaging findings of thoracic diseases have been referred—on chest radiographs or CT scans—to signs, symbols, or naturalistic images. Most of these imaging findings include the air bronchogram sign, the air crescent sign, the arcade-like sign, the atoll sign, the cheerios sign, the crazy paving appearance, the comet-tail sign, the darkus bronchus sign, the doughnut sign, the pattern of eggshell calcifications, the feeding vessel sign, the finger-in-gloove sign, the galaxy sign, the ginkgo leaf sign, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 83 publications
0
40
0
7
Order By: Relevance
“…This is in line with the current knowledge that recognizes the Usual Interstitial Pneumonia (UIP) pattern as the most common ILD in AAV [91]. For this reason, we considered it appropriate to include ANCA in the first-line exams for the diagnosis of ILD patients, mainly if with a UIP pattern or imaging resembling sarcoidosis [92].…”
Section: First-line Autoimmunity Examsmentioning
confidence: 52%
“…This is in line with the current knowledge that recognizes the Usual Interstitial Pneumonia (UIP) pattern as the most common ILD in AAV [91]. For this reason, we considered it appropriate to include ANCA in the first-line exams for the diagnosis of ILD patients, mainly if with a UIP pattern or imaging resembling sarcoidosis [92].…”
Section: First-line Autoimmunity Examsmentioning
confidence: 52%
“…6 Furthermore, higher proportion of progressive patients showed crazy-paving sign which reflects interstitial thickening. 18 Guan et al also reported higher proportion of severe patients with interstitial abnormalities. 5 The binding of COVID-19 spike protein to the receptor angiotensin converting enzyme II (ACE2) contributes to the downregulation of ACE2, increased pulmonary capillary permeability, and diffuse alveolar damage during NCP.…”
Section: Discussionmentioning
confidence: 91%
“…For the radiological assessment, all patients underwent a HRCT with a thickness ranging between 0.625 and 1.25 mm. The presence of GGO and HC, as well as the description of prevalent patterns, were performed by experienced pulmonologists and radiologists according to the current guidelines [15]. The quantification of pulmonary disease was made according to the Wells score [9]: the scans were reviewed in five levels corresponding to the origin of the great vessels, carina, pulmonary venous confluence, one centimetre above the right hemidiaphragm and between the lasts two levels.…”
Section: Methodsmentioning
confidence: 99%